1983
DOI: 10.1128/iai.40.1.166-171.1983
|View full text |Cite
|
Sign up to set email alerts
|

Vwa+ phenotype of Yersinia enterocolitica

Abstract: Expression of the Vwa+ phenotype of Yersinia pestis in vitro is known to reflect maximum induction of virulence (or V and W antigens) at 37°C with concomitant restriction of cell division. Both phenomena are potentiated by 20 mM Mg2' and prevented by cultivation at 26 or 37°C with 2.5 mM Ca2+. We have now compared this classic plasmid-mediated phenotype with those of Vwa+ Yersinia pseudotuberculosis and Yersinia enterocolitica which, unlike Y. pestis, produce ancillary outer membrane peptides unrelated to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 39 publications
4
63
1
Order By: Relevance
“…As pathogenic Yersinia harbour a 65-70 kb virulence ptasmid (reviewed by Perry and Brubaker, 1983;Skurnik, 1985; Cornelis e/a/., 1989) it could be possible that pattern B and the cleavage activity were associated with the plasmid. This was not the case, since plasmid-cured isogenic strains also had pattern B (Fig.…”
Section: No Association Of Pattern B Of 23s Rrna With the Virulence Pmentioning
confidence: 99%
“…As pathogenic Yersinia harbour a 65-70 kb virulence ptasmid (reviewed by Perry and Brubaker, 1983;Skurnik, 1985; Cornelis e/a/., 1989) it could be possible that pattern B and the cleavage activity were associated with the plasmid. This was not the case, since plasmid-cured isogenic strains also had pattern B (Fig.…”
Section: No Association Of Pattern B Of 23s Rrna With the Virulence Pmentioning
confidence: 99%
“…The two main mechanisms for phagocytic uptake occur (i) via complement receptor type three (CR3), which recognizes the complement fragments C3b and C3bi, and (ii) via the Fc receptor, which recognizes the Fc-part of immunoglobulins . Yersinia resists phagocytosis via CR3 by avoiding deposition of the opsonizing fragments C3b and C3bi (Perry and Brubaker, 1983;China et a/., 1993;. The Fc receptor-mediated process is blocked via a Yop-mediated phagocytic inhibition that is similar to that seen during the uptake of nonopsonired bacteria (Fallman et a/., 1995).…”
Section: Introductionmentioning
confidence: 99%
“…We also suggest that resistance to phagocytosis and catalase production activity are important for determining the pathogenicity of Y. pseudotuberculosis for the following reason. Resistance to phagocytosis is an important factor in the pathogenicity of Yersinia organisms; the existence of this factor stimulates infectivity and this brings about an infectious disease called yersiniosis (38)(39)(40)(41)53). It has been shown that the resistance of Yersinia organisms to phagocytosis depends on outer-membrane proteins encoded by virulence plasmids (6,7,10,36,47).…”
Section: Discussionmentioning
confidence: 99%